A new pea variety ‘Krasnoufimsky 20’ - L. I. Likhacheva; A. V. Moskalev; N. V. Likhacheva; N. N. Matolinets (Зерновое хозяйство России, 2024)
Work on developing a new pea variety ‘Krasnoufimsky 20’ began in 2008 on the experimental fields of the Krasnoufimsky breeding center of the Ural Research Institute of Agriculture, a branch of the FSBSI UrFARC UrO RAS. The purpose of the current study was to develop a highly productive pea variety that is resistant to negative environmental conditions, resistant to diseases and pests, and has a non-lodging stem and non-shedding seeds. The greatest productivity excess of the variety ‘Krasnoufimsky 20’ compared to the standard was observed in 2017, 2019, 2021 and 2022 (from 11 % to 62 %). On average, ‘Krasnoufimsky 20’ gave a significant excess over the standard by 0.26 t/ha. The variety ‘Krasnoufimsky 20’ requires weather conditions in the HTC range of 1.0–2.1 to obtain stable productivity. But regardless of environmental factors, both in favorable conditions and during periods of waterlogging or drought, the variety ‘Krasnoufimsky 20’ exceeded the standard by 0.03–0.83 t/ha. The variety ‘Krasnoufimsky 20’ ripened 1–3 days earlier than the standard, it has a larger number of beans and seeds per plant (by 0.2 and 1.5 pieces, respectively). The variety ‘Krasnoufimsky 20’ has a high seed productivity per plant (2.3 g). The variety is affected with ascochyta blight and root rot at the standard level, its damage by the codling moth is less than the standard. The new variety ‘Krasnoufimsky 20’ exceeded the standard variety Krasnoufimsky 11 and other varieties of local breeding according to adaptability. In 2023, it was decided to include the new pea variety ‘Krasnoufimsky 20’ in the State List of Breeding Achievements approved for use in the regions of Volga-Vyatka, North Caucasus, Ural, West Siberian.